Diversities of Calreticulin Gene Mutations in Macedonian Patients With Essential Thrombocythemia - Panovska Stavridis, Irina; Eftimov, Aleksandar; Ivanovski, Martin; Stojanovic, Aleksandar; Georgievski, Borche; Chevrevska, Lidija; Dimovski, Aleksandar (Elsevier BV, 2016)
Acquired calreticulin (CALR) gene mutations are one of the molecular hallmarks of essential thrombocythemia (ET). It has been suggested that patients with ET with CALR mutations are associated with a distinct clinical phenotype.